Anisotropy in Shape and Ligand‐Conjugation of Hybrid Nanoparticulates Manipulates the Mode of Bio–Nano Interaction and Its Outcome. (4th May 2017) - Wang, Xiaoyou; Lin, Li; Liu, Renfa; Chen, Min; Chen, Binlong; He, Bo; He, Bing; Liang, Xiaolong; Dai, Wenbing; Zhang, Hua; Wang, Xueqing; Wang, Yiguang; et al.
Abstract : In an attempt to manipulate the biological features of nanomaterials via both anisotropic shape and ligand modification, four types of nanoparticulates with good morphological stability are designed and engineered, including hybrid nanospheres, nanodiscs, and nanodiscs with edge modification or plane modification of octa‐arginine (R8) sequence. It is found that the R8 modification anisotropy can trigger huge differences in the endocytosis, intracellular trafficking, and even tissue penetration of nanoparticulates. From plane modification to edge modification of R8, the maximum increase in cell uptake is up to 17‐fold, which is much more significant than shape anisotropy alone. On the other hand, six types of different cell lines are investigated to simulate biological microenvironment. It is demonstrated that the maximum difference in cell uptake among six cell lines is 12‐fold. Three main driving forces are found to contribute to such bio–nano interactions. Based on the findings of this study, it seems possible to manipulate the biointeraction mode of nanomaterials and its output by regulating their anisotropy in both shape and ligand modification. Abstract : Nanospheres, nanodiscs, and nanodiscs with edge modification or plane modification of octa‐arginine sequence are prepared. From nanospheres to nanodiscs and from plane modification to edge modification, the cellular uptake increases 1.5‐ and 17‐fold, respectively. Such alternations also affect the intracellular pathway and tumor penetration. The double effect of anisotropic shape and ligand‐modification is significant and might be applied to manipulate the nanovector delivery.